Marginaliseret tid: Materialitet, fremtid og håb i Georgien - Frederiksen, Martin Demant (Tidsskriftet Antropologi, 2011)
Martin Demant Frederiksen: Marginaliseret tid – materialitet, fremtid og håb i Georgien For arbejdsløse unge i Georgien byder fremtiden på få muligheder. Selv om den georgiske regering gang på gang proklamerer, at fremtiden for landet er lys, føler mange unge ikke, at det er en fremtid, som de er en del af. Denne artikel beskriver en række statslige byggeprojekter i det vestlige Georgien og måderne, hvorpå disse bliver omtalt af regeringen og lokale unge i forhold til fremtiden. Artiklen argumenterer for, at selv om byggerierne fra officiel side er ment som konkretiseringer af en lovende fremtid, bidrager de til en følelse af marginalisering blandt unge i regionen. Martin Demant Frederiksen: Temporal Marginalization. Materiality, Future and Hope in the Republic of Georgia Massive unemployment and widespread poverty have been part of daily life for large parts of the Georgian population since the country gained independence in 1991. For many unemployed youth in Georgia, the future is marked by a lack of possibilities. Despite the fact that the Georgian government continually stresses that the country’s future is bright, many young people feel that this presumed future is one that they are not part of. This article describes a series of state-sponsored construction projects in the coastal city Batumi in Western Georgia, and the ways in which these are spoken of in relation to the future by the government and local youth in the city respectively. The article argues that despite the fact that the buildings are intended as concretizations of a promising future, their presence contributes rather to experiences of marginality among youth in the region. Keywords: Youth, future, materiality, Republic of Georgia, marginality